Development of direct to indirect cost ratio of occupational accident for manufacturing industry - Mohd. Rohani, Jafri (2015)
Occupational injury would certainly give an impact not just to the victim but also to the organization and society at large. The impact would be in term of victim suffering, bad company reputation, low working moral among fellow workers and economic costs to the company. However, most of the aspects are difficult to quantify except for economics costs. The objective of this paper is to validate relationship accident direct cost model towards its observable cost components. Besides, this paper also proposes direct to indirect cost ratio based on accident cost range, accident scenario and impact of accident. Basically, accident cost can be categorized into two distinct categories which are direct and indirect cost. A total of 342 cases have been acquired for this study and recorded cases only cover temporary disability with more than one day of MC. Data is gathered from six types of sectors from manufacturing industry in Malaysia by using local specific method. The validity of direct cost model is tested by using confirmatory factor analysis (CFA) while indirect to indirect cost ratio is developed based on following aspects: (1) Accident cost range; (2) Accident scenario; and (3) Impact of accident. Proven direct cost model and direct to indirect cost ratio proposed would give a better insight to the relevant stakeholder in quantifying the occupational accident cost which may assist them in making necessary changes in order to avoid occurrence of similar accident in the future.